Indonesian Textbook Based on Character Education Through Active Learning for the Elementary School Students - Winarni, Retno; Slamet, St Y; Syawaludin, Ahmad (Universitas Pendidikan Ganesha, 2022)
The lack of success in learning Indonesian in fifth-grade elementary schools is dominant in the low productive language skills. The limitations of learning resources such as textbooks are one of the causes of the emergence of these problems. This study aims to develop Indonesian language textbooks containing character education through the Active Learning model by utilizing literature as a learning resource. The type of research used is development research with the following stages: exploration, model development, and model testing. The subjects of this research were the fifth-grade elementary school students at the exploration stage, as many as 30 students. At the development stage, as many as 56 students and as many as 165 students at the testing stage. Data was collected through documentation studies, observations, interviews, and questionnaires. The data analysis technique was conducted qualitatively using an interactive model at the exploration and product development stages. The statistical analysis used an independent sample t-test at the model test stage. The test begins with prerequisite analysis and hypothesis testing. The research results at the exploration stage showed that the textbooks used were not by the needs of elementary school students and teachers, then a needs analysis and development of a textbook prototype were carried out. At the stage of testing the effectiveness with the main field trial, it showed a difference between the experimental and control groups. The study concludes that Indonesian language textbooks are stated to improve student's language skills in elementary school. The use of textbooks is recommended to support effective language learning.Â